"It's his cheerfulness that gives me hope": A qualitative analysis of access to pediatric cancer care in Northern Tanzania. - Madeline Metcalf; Happiness D Kajoka; Esther Majaliwa; Anna Tupetz; Catherine A Staton; João Ricardo Vissoci; Pamela Espinoza; Cesia Cotache-Condor; Henry E Rice; Blandina T Mmbaga; Emily R Smith (PLOS Global Public Health)
Pediatric cancer is a significant and growing burden in low- and middle-income countries. The objective of this project was to describe the factors influencing access to pediatric cancer care in Northern Tanzania using the Three Delays Model. This was a cross-sectional qualitative study conducted between June and August 2023 at Kilimanjaro Christian Medical Centre (KCMC). Using purposive sampling methods, caregivers of children obtaining pediatric cancer care at KCMC were approached for participation in in-depth interviews (IDIs) and a demographic survey. All IDIs were facilitated in Swahili by a bilingual research coordinator. Analysis utilized inductive and deductive coding approaches to identify dominant themes and sub-themes impacting access to pediatric oncology care. Data collection concluded once saturation was achieved at 13 IDIs, defined as the absence of new codes after three consecutive interviews. Participants reported significant financial barriers to accessing pediatric cancer care along the entire care continuum. In the first delay, themes included waiting for symptoms to resolve and the identification of initial symptoms. The most substantial delays occurred in delay 2, including health infrastructure at mid-level facilities, misdiagnoses, the referral system, travel, and traditional medicine. Participants did not describe delays after arrival to KCMC and rather offered perspective on their child's cancer diagnosis, their concerns while obtaining care, and their hopes for the future. Financial support provided by the Tanzanian government was the only facilitator noted by participants. We suggest targeted interventions including 1) empowerment of CHWs and local traditional healers to advocate for earlier care seeking behavior, 2) implementation of clinical structures and training at intermediary medical centers aimed at earlier referral to a treatment facility, 3) incorporation of support and education initiatives for families of children with a cancer diagnosis. Lastly, national health plans should include pediatric cancer care.